2022
DOI: 10.1186/s12986-022-00669-1
|View full text |Cite
|
Sign up to set email alerts
|

Protective effect of homogeneous polysaccharides of Wuguchong (HPW) on intestinal mucositis induced by 5-fluorouracil in mice

Abstract: Background In hospitalized patients, drug side effects usually trigger intestinal mucositis (IM), which in turn damages intestinal absorption and reduces the efficacy of treatment. It has been discovered that natural polysaccharides can relieve IM. In this study, we extracted and purified homogenous polysaccharides of Wuguchong (HPW), a traditional Chinese medicine, and explored the protective effect of HPW on 5-fluorouracil (5-FU)-induced IM. Methods and results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 57 publications
0
14
0
Order By: Relevance
“…Therefore, the increase of serum DAO can reflect the damage degree of the intestinal mucosa. 21 In addition, the plasma d -LAC level was initially proposed as a marker for the diagnosis of bacterial infection. In the case of intestinal barrier dysfunction, the levels would rise due to increased intestinal mucosal translocation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, the increase of serum DAO can reflect the damage degree of the intestinal mucosa. 21 In addition, the plasma d -LAC level was initially proposed as a marker for the diagnosis of bacterial infection. In the case of intestinal barrier dysfunction, the levels would rise due to increased intestinal mucosal translocation.…”
Section: Discussionmentioning
confidence: 99%
“…The intestinal permeability was determined using the concentrations of DAO and d -LAC as mentioned in Shi et al , and also using ELISA kits. 21…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, recent research data demonstrate that polysaccharides extracted from some natural products have a positive effect in treating AD-like skin lesions in mice and humans ( Wu et al, 2011 ; Nam et al, 2013 ; Lin et al, 2017 ; Ashigai et al, 2018 ; Motoyama et al, 2018 ; Tian et al, 2019 ). In previous studies, the polysaccharide extracted from Wuguchong (PEW) was found as a bioactive ingredient to prevent obesity and relieve intestinal inflammation caused by drug side effects, partly through the modulation of inflammatory responses ( Wang et al, 2020 ; Shi et al, 2022 ). However, the effect of PEW on AD has not been investigated so far.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, the polysaccharide extracted from Wuguchong (PEW) was found to be useful in reducing high-fat diet-induced obesity in mice through regulation of the intestinal microbiota composition ( Wang et al, 2020 ). Besides, homogeneous polysaccharides of Wuguchong showed a protective effect on the intestinal mucosa and can relieve 5-fluorouracil-induced intestinal inflammation in mice ( Shi et al, 2022 ). As previously discussed, some polysaccharides were proven to be effective in ameliorating AD symptoms in mice or humans.…”
Section: Introductionmentioning
confidence: 99%
“…TNFα, in turn, activates NF-κB. This positive feedback mechanism results in signal amplification and increased production of inflammatory mediators, which eventually destroy the intestinal mucosal barrier and lead to the formation of mucosal ulcers ( Huang et al, 2022 ; Shi et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%